2022
DOI: 10.1093/jalm/jfac004
|View full text |Cite
|
Sign up to set email alerts
|

One Swab Fits All: Performance of a Rapid, Antigen-Based SARS-CoV-2 Test Using a Nasal Swab, Nasopharyngeal Swab for Nasal Collection, and RT–PCR Confirmation from Residual Extraction Buffer

Abstract: Background Point-of-care SARS-CoV-2 antigen tests have great potential to help combat the COVID-19 pandemic. In the performance of a rapid, antigen-based SARS-CoV-2 test (RAT), our study had 3 main objectives: to determine the accuracy of nasal swabs, the accuracy of using nasopharyngeal swabs for nasal collection (nasalNP), and the effectiveness of using residual extraction buffer for real-time reverse-transcriptase PCR (RT–PCR) confirmation of positive RAT (rPan). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Among the 49 studies on nasal swabs containing 79,073 samples [ [2] , [3] , [4] , 6 , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] ], all of them were published between 2021 and 2022, and twenty-one studies were conducted in the USA [ 12 , 14 , 15 , 18 , 21 , 22 , [25] , [26] , [27] , [32] , [33] , [34] , [35] , 39 , 44 , 45 , [47] ...…”
Section: Resultsmentioning
confidence: 99%
“…Among the 49 studies on nasal swabs containing 79,073 samples [ [2] , [3] , [4] , 6 , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] ], all of them were published between 2021 and 2022, and twenty-one studies were conducted in the USA [ 12 , 14 , 15 , 18 , 21 , 22 , [25] , [26] , [27] , [32] , [33] , [34] , [35] , 39 , 44 , 45 , [47] ...…”
Section: Resultsmentioning
confidence: 99%
“…Differences in study settings, population immunity, epidemiological context, and workload at health facilities could have caused some of the differences in assay performance observed in our study. Evaluations performed in clinical settings and populations from Canada, United Kingdom, United States, and Germany reported discrepant sensitivities [ 24 , 25 , 26 , 27 ]. For example, in United Kingdom, in ambulance services and walk-through testing settings, Cubas-Attienzar et al (2021) evaluated the COVIOS nasal antigen SARS-CoV-2 rapid tests and found a higher sensitivity and specificity, of 85.0% and 97.8%, respectively [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a study showed that the residual buffer left over from a rapid SARS-CoV-2 test could be used to confirm a positive result through RT-PCR. 9 Another study demonstrated that WGS could be performed on both residual nasal swabs and the positive line on a lateral flow assay. 8…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of using a residual nasal swab (rNS) for molecular testing, following preparation for and performance of rapid testing, is not well understood, but a couple studies have showed that a rNS may be sufficient for performing RT-PCR and WGS on prospective SARS-CoV-2 specimens. 8,9 To determine whether a single anterior nasal swab is sufficient for confirming rapid influenza diagnostic test (RIDT) results, we performed RT-PCR on paired NP/OP and rNS specimens collected from patients of all ages in primary care clinics. Additionally, we performed WGS on a subset of paired specimens.…”
Section: Introductionmentioning
confidence: 99%